Caracterización socio económica y productiva de la parroquia Eloy Alfaro, cantón Latacunga, provincia de Cotopaxi 2022. - Caguana Chango, Alan Francisco (2022)
This research work is based on the "SOCIO-ECONOMIC AND PRODUCTIVE CHARACTERIZATION OF THE ELOY ALFARO PARISH, LATACUNGA CANTON, COTOPAXI PROVINCE 2022." emphasizing the socio-economic productive diagnosis to understand the dynamics of life and production of the residents of the Eloy Alfaro parish through its economic, social and productive characteristics with the help of surveys with different indicators, the lack of knowledge of the reality of life and production of the residents of the parish has resulted in little deficiency in the intervention to improve the socioeconomic and productive conditions of the sector being studied, the results obtained from the research are as follows: In the characteristics of the population in gender there are more| women than men, where the family nuclei are 3 to 4 people, most families with at least two children and an older adult per household, it can be seen that security is a problem that people suffer from the theft of their animals, house or armed robbery. Therefore, the distrust of people at the time of conducting the surveys, but nevertheless, the economic activity with the highest percentages is agriculture, livestock, and forestry with 25%. They also have production areas, which are used for raising animals and crops, the products obtained are used for consumption and sale, of the person. The diagnosis made shows the different problems experienced by the residents of the parish under study and thus can take action on the problems encountered, by establishing programs or projects that change this reality.